Generation of Weak Double Layers and Low-Frequency Electrostatic Waves in the Solar Wind - Lakhina, G.S.; Singh, S.V. (Solar Physics, 290, p. 3033–3049, doi: 10.1007/s11207-015-0773-1, 2015)
We propose that the mechanism for the generation of weak double layers (WDLs) and low-frequency coherent electrostatic waves, observed by Wind in the solar wind at 1 AU, might be slow and fast ion-acoustic solitons and double layers. The solar wind plasma is modelled as a fluid of hot protons and hot α particles streaming with respect to protons, and suprathermal electrons having a κ-distribution. The fast ion-acoustic mode is similar to the ion-acoustic mode of a proton–electron plasma and can support only positive-potential solitons. The slow ion-acoustic mode is a new mode that occurs due to the presence of α particles. This mode can support both positive and negative solitons and double layers. The slow ion-acoustic mode can exist even when the relative streaming, U0, between α particles and protons is zero, provided that the α temperature, Ti, is not exactly equal to four times the proton temperature, Tp. An increase of the κ-index leads to an increase in the critical Mach number, maximum Mach number, and the maximum amplitude of both slow and fast ionacoustic solitons. The slow ion-acoustic double layer can explain the amplitudes and widths, but not the shapes, of the observed WDLs in the solar wind at 1 AU by Wind spacecraft. The Fourier transform of the slow ion-acoustic solitons/double layers would produce broadband low-frequency electrostatic waves having main peaks between 0.35 kHz to 1.6 kHz, with an electric field in the range of E = (0.01 – 0.7) mV m−1, in excellent agreement with the observed low-frequency electrostatic wave activity in the solar wind at 1 AU.
Keywords: Solar wind; Shock waves; Waves; Plasma; Plasma physics